Physiological responses during the long-distance race in the warm environment in runners: a pilot-study - Coelho Rodrigues Jr, F.; Prado, D. M.; Sena, A. F.; Veneroso, C. E.; Cabido, C. E.; Sevílio Jr, M. N. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: This study investigated the effects of warm temperature in the external environment on physiological response in self- pace during the long-distance race in runners and the association between the physiological index of endurance performance (i.e., speeds at ventilatory anaerobic threshold [VVAT], respiratory compensation [VRCP], maximum oxygen uptake [VVO2max], and running economy) and average pace for each 3-km during the 21-km race. METHODS: Five male recreational runners (mean±SE age 36.6±6.1 years; VO2 max: 59.2±7.9) were submitted to a 21-kilometers race in the outdoor environment using a portable metabolic analyzer. RESULTS: Our results showed a reduction in speed to kilometers 12, 15, 18 and 21 than kilometer 3 (P<0.05). The runners showed a decrease in both VO2 (mL/kg/min) and RER from kilometer 15 (P=0.001 and P=0.003, respectively). Regarding cardiovascular response, our data demonstrated a steady HR response from kilometer 6 to 21 (P=0.99). Otherwise, the runners showed a decrease in oxygen pulse from kilometer 9 than both kilometers 3 and 6 (P=0.001). During the race, the runners demonstrated a significant increase in body temperature compared to rest (P=0.001). The results of the correlation analysis between physiological index of endurance performance and average pace for each 3-km during the 21-km race showed significant correlation between VVAT and average pace for: 12-km (r=0.95; P=0.01), 15-km (r=0.89; P=0.05) and 21-km (r=0.86; P=0.04); VRCP and average pace for 3-km (r=0.88; P=0.05). CONCLUSIONS: Our findings demonstrated that the increase in body temperature in a warm environment during the 21-km race is associated with both cardiovascular and metabolic strain in runners. Concerning physiological markers of endurance performance, VVAT appears to be the best predictor of the average pace throughout the 21-km race in a warm environment in recreational runners.